ASSESSING THE PERFORMANCE OF STUDENTS WITH DIFFERENT BACKGROUND AND STUDYING CERAMICS - Samuel Nortey; Robert Amoanyi; Emmanuel Eyram Donkor (JADECS (Journal of Art, Design, Art Education and Culture Studies), 2023)
For almost a decade, the Ghanaian educational system for ceramics studies at the tertiary level has allowed senior high students with various academic backgrounds to specialize in ceramics at the tertiary level. Though a very laudable idea, there has yet to be an assessment of their performance in a studio-oriented ceramic programme to inform policy and institutional decisions. This study, therefore, assesses the performance of ceramic students with diverse academic backgrounds. The study used quantitative and qualitative approaches, revealing that students with no background in art struggle with ceramic studio assignments, especially those that studied Home Economics and General Arts. Though students with a Science background appear to do well in the soil science-related courses of ceramics, there are still challenges with art concepts and art history. It is recommended that there is a need for counseling and orientation of mind for students who did not choose ceramics as their first choice and those without art backgrounds.